Institutional Failures in Decentralization: Insight from Batam, Indonesia - Zaenuddin, Muhammad; Kumorotomo, Wahyudi; Erlangga, Irwita (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2024)
Batam’s development began in 1970 by the Batam Authority (now called BP Batam) and was projected as an industrial area. At that time, Batam was transformed into a city with growth above the average national economic growth. Yet, the contrasting situation occurred after the implementation of regional autonomy in Batam. The presence of the Batam City Government as an executor of regional autonomy has a very strong legal and political position. Therefore, this paper focuses on institutional failures which have implications for the decline of the economy during the decentralized era. The methodology used in this research is descriptive exploratory, which extracts information from primary and secondary data. Primary data was obtained using surveys and interviews with expert informants. The data was analyzed using the Delphi method and Analytical Hierarchy Process (AHP). The results of the study showed that the problem was institutional dualism between the Batam City Government and BP Batam, which had implications for legal uncertainty. The Delphi method resulted in recommendations for the Free Trade Zone (FTZ), Special Economic Zones (SEZ), and the implementation of special autonomy in Batam. Meanwhile, the Analytical Hierarchy Process (AHP) method resulted in a finding that special autonomy was the best policy choice. The concept of asymmetric decentralization based on economics is a possible model of special autonomy. However, in its implementation, further stages are needed to prepare a special law regarding the substance of specialization given to Batam.